2021
DOI: 10.1186/s12906-021-03323-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and anti-biofilm activity of a new Spanish extract of propolis against Candida glabrata

Abstract: Background Resistance to traditional antifungal agents is a considerable health problem nowadays, aggravated by infectious processes related to biofilm formation, usually on implantable devices. Therefore, it is necessary to identify new antimicrobial molecules, such as natural products, to develop new therapeutic strategies to prevent and eradicate these infections. One promising product is propolis, a natural resin produced by honeybees with substances from various botanical sources, beeswax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
7
1
Order By: Relevance
“…Propolis extract was previously shown to significantly reduce total biomass and the number of viable bacterial cells, and it was shown that the cells were damaged and disorganized both in the planktonic cells and sessile biofilm cells caused by treatment with propolis [ 43 ]. The good antimicrobial activity and moderate antibiofilm activity reported here is contrary to the good antibiofilm activity of propolis extracts reported against gram-positive and gram-negative bacteria, which effectively reduce or eliminate biofilms and planktonic cell growth [ 31 , 44 , 45 ]. However, moderate to low susceptibility of biofilms to propolis extracts were reported by other researchers [ 46 , 47 ] and hence are in conformity with our results.…”
Section: Discussioncontrasting
confidence: 88%
“…Propolis extract was previously shown to significantly reduce total biomass and the number of viable bacterial cells, and it was shown that the cells were damaged and disorganized both in the planktonic cells and sessile biofilm cells caused by treatment with propolis [ 43 ]. The good antimicrobial activity and moderate antibiofilm activity reported here is contrary to the good antibiofilm activity of propolis extracts reported against gram-positive and gram-negative bacteria, which effectively reduce or eliminate biofilms and planktonic cell growth [ 31 , 44 , 45 ]. However, moderate to low susceptibility of biofilms to propolis extracts were reported by other researchers [ 46 , 47 ] and hence are in conformity with our results.…”
Section: Discussioncontrasting
confidence: 88%
“…Antifungal activities of various extracts of propolis have been examined against several yeasts, such as Candida albicans, C. dubliniensis, C. glabrata, C. krusei, C. parapsisolis, C. tropicalis, Saccharomyces cerevisiae [13,[16][17][18]21,50,[54][55][56][57][60][61][62][63][64], as well as against molds, such as Alternaria solani, Alternaria alternata, Aspergillus niger, Aspergillus ochraceus, Botrytis cinerea, Cladosporium spp., Fusarium solani, Fusarium oxysporum, Mucor mucedo, Penicillium digitatum, Penicillium expansum, Penicillium chrysogenum, Rhizopus stolonifera, Rhodotorula mucilaginosa and Trichophyton spp. [9,19,43,64].…”
Section: Antifungal Properties Of Propolismentioning
confidence: 99%
“…Oki ńczyc et al [50] showed that ethanolic extract of propolis inhibited filamentation of cells of C. albicans, germination of yeasts and increased production of the superoxide anion radical. A few studies showed that extracts of propolis are effective inhibitors of biofilm [16,53,54,57,[67][68][69]. Freires et al [54] observed that ethanolic extract of Brazilian propolis (types 3 and 13) can lead to disruption of the biofilm structures of Candida sp.…”
Section: Antifungal Properties Of Propolismentioning
confidence: 99%
See 2 more Smart Citations